Rethinking Indonesia’s Legislative Drafting Style: Codification, Omnibus Legislation, and the Limits of the Guide of Legislation - Fitriani Ahlan Sjarif; Efraim Jordi Kastanya; Aditya Wahyu Saputro (Sriwijaya Law Review, 2026)
Indonesia's legislative drafting framework requires all laws and regulations to comply with the Guide of Legislation because non-compliance may result in judicial invalidation. Although legislative drafting is expected to adhere to these formal standards, recent codification and omnibus law-making have introduced new drafting techniques that are not expressly accommodated within the existing framework. Despite extensive discussion of codification and omnibus legislation, limited attention has been paid to their compatibility with Indonesia's legislative drafting rules and the consequences for legal certainty and legislative validity. This article examines whether the 2023 Penal Code and the Job Creation Law conform to the drafting standards outlined in Law Number 12 of 2011 and explores the implications of any deviations. The study employs doctrinal legal research, using statutory and case analyses of the 2023 Penal Code, the Job Creation Law, and relevant legislative drafting principles. The findings reveal that both legislative models create tensions with the prescribed drafting framework. The Penal Code departs from the required structure of general provisions, while omnibus legislation obscures amendment history and adopts purposive naming that may diminish legislative transparency. The article argues that every legislative drafting innovation should first be formally institutionalised within the Guide of Legislation before its implementation to safeguard clarity, legal certainty, and the constitutional validity of enacted laws.